Predictors of Satisfaction With Childbirth Services Amongst Postnatal Women in Two Selected Teaching Hospitals in Ogun State, Nigeria - OJO, Eunice Abimbola; AGBONJIMI, Lawrence Adewale; AINA, Rachel Omolara; ALABI, Praise Oladeji (Advances in Social Sciences Research Journal, 2021)
Satisfaction with childbirth service is a multi-dimensional construct embracing satisfaction with self (personal control), and with the physical environment of delivery ward and quality of care. Maternal health care service encompasses family planning, preconception, antenatal, delivery and postnatal care. Goals of preconception care include providing education, health promotion, screening tests for various health problems and interventions for women of reproductive age to reduce risk factors that might affect future pregnancies. Women who begin prenatal care early in their pregnancies have better birth outcomes than those who receive little or no care during their pregnancies. This study was conducted to identify predictors of satisfaction with childbirth services and the factors influencing them. A well-structured questionnaire was used to get responses from 81 postnatal women in OOUTH and BUTH. Data was analyzed using Statistical Package for Social Science. Descriptive and inferential statistics were used in analyzing the research questions and hypotheses respectively. Majority of the participants revealed good level of satisfaction with most child birth services rendered by the two selected teaching hospitals, but more than two-third of the respondent’s claims, dissatisfaction in pain control and baby care after birth in the two hospitals. Findings revealed more satisfaction towards child birth services in BUTH than OOUTH, this might be as a result of inadequate equipment, structural facilities and poor waiting areas in the public hospital. It was recommended among others that Government should facilitate focused antenatal care, institutional delivery and postnatal care in terms of reducing maternal and neonatal mortality.